A Collaborative Learning Guidance Program Based on Need Analysis of Students’ Learning Motivation and Behavior - Atmoko, Adi; Hanafi, Husni; Wahyuni, Eny Tri; Barida, Muya (Psikopedagogia, 2022)
The purpose of this study was to develop a collaborative guidance and counseling program based on the need analysis of student’s learning motivation and behavior. A survey design was selected to describe, measure, and analyze the relationship between achievement motivation, religious motivation, affiliation motivation, and the need for power on students’ learning behavior. The study population was 795 students in a school, and 595 students were recruited using a stratified random sampling technique to represent the 7th, 8th, and 9th-grade students. Data were collected using achievement motivation, religious motivation, affiliation motivation, need for power, and learning behaviors with minimum item-total validity of 0.30 and reliability score between 0.6 and 0.9. The data were analyzed using descriptive statistics and Pearson Correlation, supported by expert statements and relevant previous findings, as well as logical analysis for relevant program recommendations. The result showed that all motivations, except power motivation, are significantly related to students learning behavior. Thus, collaborative learning guidance and counseling program is suggested to cover the strengthening of religious motivation, achievement motivation, and learning behavior. It is also necessary to optimize online and offline media for service targets, including individuals, groups, classes, a whole school, and collaboration with external parties. The collaborative effort should include the school principal, homeroom teacher, subject teacher, administrators, students organization, experts, and parents. This study may serve as a reference for school counselors in providing guidance services for students.